Can Patients Trust Online Health Information? A Meta-narrative Systematic Review Addressing the Quality of Health Information on the Internet - Daraz, Lubna; Morrow, Allison S.; Ponce, Oscar J.; Beuschel, Bradley; Farah, Magdoleen H.; Katabi, Abdulrahman; Alsawas, Mouaz; Majzoub, Abdul M.; Benkhadra, Raed; Seisa, Mohamed O.; Ding, Jingyi (Francess); Prokop, Larry; et al. (Journal of general internal medicine : JGIM, 2019)
Background The Internet has become a leading source of health information accessed by patients and the general public. It is crucial that this information is reliable and accurate. Objectives The purpose of this systematic review was to evaluate the overall quality of online health information targeting patients and the general public. Methods The systematic review is based on a pre-established protocol and is reported according to the PRISMA statement. Eleven databases and Internet searches were performed for relevant studies. Descriptive statistics were used to synthesize data. The NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies was used to assess the methodological quality of the included studies. Results Out of 3393 references, we included 153 cross-sectional studies evaluating 11,785 websites using 14 quality assessment tools. The quality level varied across scales. Using DISCERN, none of the websites received a category of excellent in quality, 37–79% were rated as good , and the rest were rated as poor quality. Only 18% of websites were HON Code certified. Quality varied by affiliation (governmental was higher than academic, which was higher than other media sources) and by health specialty (likely higher in internal medicine and anesthesiology). Conclusion This comprehensive systematic review demonstrated suboptimal quality of online health information. Therefore, the Internet at the present time does not provide reliable health information for laypersons. The quality of online health information requires significant improvement which should be a mandate for policymakers and private and public organizations.